Meningkatkan Kemampuan Desain Iklan Produk bagi Pengusaha Muslim Indonesia (IPEMI) Medan Menggunakan Aplikasi Berbasis Android - Aninda Muliani; Triase Triase; Adnan Buyung Nasution; Samsudin Samsudin; Suendri Suendri (Jurnal IPTEK Bagi Masyarakat, 2021)
The development of digital technology, especially digital multimedia, can change the way people do business. The development of social media and the sophistication of new applications offer endless opportunities for product marketing. Product marketing strategy is needed to increase competitiveness. One of the marketing strategies is attractive advertising media. This community service aims to improve the ability of home industry entrepreneurs who are members of the Medan IPEMI (Indonesian Islamic Entrepreneurs Association) organization to promote their products through advertising media. This activity teaches women entrepreneurs how to use the Kinemaster app to create product ads with visually appealing content. The resulting media is in the form of moving advertisements in short duration video formats.